Seasonal variation in the role of grey squirrels as hosts of Ixodes ricinus, the tick vector of the Lyme disease spirochaete, in a British woodland - Craine, N G; Randolph, S E; Nuttall, P A (Folia parasitologica, 1995)
Data are presented on the variable patterns of the seasonal dynamics of Ixodes ricinus L. ticks seen questing on the vegetation and feeding on small rodents (mice and voles) and squirrels within a British woodland focus of Lyme borreliosis. Information on tick infestation levels on pheasants is also presented. The results show a prolonged, unimodal pattern of tick activity, with ticks feeding throughout the year in this sheltered habitat. If host density is taken into account, squirrels are quantitatively more important than small mammals as hosts for larval ticks from April until July, and overwhelmingly so for nymphal ticks throughout the year. The observed inter- and intraspecific differences in tick infestation levels are related to the behaviour of both hosts and ticks. Squirrels, as competent hosts for Borrelia burgdorferi and frequent occupants of habitats closely associated with man, will contribute significantly to the risk of Lyme disease.
Keywords: lymeská nemoc; Animals; United Kingdom; Seasons; klíště; Arthropod Vectors; Borrelia burgdorferi komplex; Spojené království; Sciuridae; roční období; Muridae; Arvicolinae; Borrelia burgdorferi Group; neparametrická statistika; členovci - vektory; Lyme Disease; Statistics, Nonparametric; zvířata; Tick Control; Ixodes; kontrola klíšťat